ANALISIS PERAN ADMINISTRATIF KANTOR URUSAN AGAMA DALAM PENETAPAN DAN PENGELOLAAN TANAH WAKAF DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH - Indarwati, Yayu; Raehana, Syarifa; Lawang, Hasanna; Akil, M; Subaedah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine and analyze the administrative role of the Office of Religious Affairs (KUA) in determining waqf land and the management of waqf land by nazhir from the perspective of Sharia Economic Law in Bolo District, Bima Regency. This study uses a qualitative research type with a phenomenological approach and a sharia approach. Data collection techniques were carried out through observation, interviews, and documentation with informants consisting of the head of KUA, waqf administration staff, nazhir, wakif, and community leaders in Bolo District. The data obtained were then analyzed descriptively qualitatively to provide a comprehensive picture of the administration and management practices of waqf land. The results of the study indicate that the administrative role of KUA in determining waqf land has been implemented through the process of verifying land ownership documents, recording waqf pledges, and issuing Waqf Pledge Deeds (AIW) as proof of legality. This procedure aims to provide legal certainty and protection for waqf assets. However, in practice, waqf is still found to be carried out verbally without official registration, as well as a lack of public understanding of the importance of the administrative aspects and legality of waqf. Meanwhile, waqf land management by the nazhir is generally used for religious and social purposes, such as the construction of mosques and educational facilities. However, this management is not yet fully optimal due to limited managerial capabilities, lack of reporting, and the absence of a structured and professional management system. From the perspective of Sharia Economic Law, this practice reflects the principle of public welfare, but still requires improvements in transparency, accountability, and professionalism to optimize the benefits of waqf for community welfare.